Mendelian randomization and drug repurposing analysis identifies APOE as a potential therapeutic target for low back pain - Jianye Yang; Weihui Qi; Dong Wang; Zhenglin Mei; Hao Pan; Yongjiang He (Medicine, 2026)
Low back pain (LBP) is a prevalent chronic pain syndrome primarily driven by spinal degeneration, causing persistent disability and reduced quality of life. Despite available interventions, identifying novel therapeutic targets remains imperative for modifying disease progression. We performed Mendelian randomization analyses integrating plasma proteomics data (4657 proteins in 7213 Europeans) and FinnGen R12 LBP Genome-wide association study (17,615 cases/420,066 controls). Robustness was confirmed via Bayesian colocalization and Steiger directionality tests. Protein-protein interaction networks, functional enrichment (Kyoto Encyclopedia of Genes and Genomes/gene ontology), single-cell annotation, and druggability assessments were subsequently applied. Mendelian randomization identified Apolipoprotein E (APOE) as causally protective against LBP (OR = 0.86, 95% CI: 0.81–0.91, P = 5.12 × 10 −7 ). Bayesian colocalization supported shared causal variants, while the Steiger test excluded reverse causation. Protein-protein interaction networks revealed interactions between APOE and established LBP drug targets. Functional analyses demonstrated APOE’s enrichment in lipid metabolism pathways (particularly cholesterol transport), with elevated expression in macrophages/fibroblasts and hepatic/cerebral tissues. Druggability assessment indicated: Glucocorticoids directly upregulate endogenous APOE; Inflammatory cytokine receptor antagonists and PPARγ agonists indirectly enhance APOE activity. Genetically elevated APOE expression reduces LBP risk, establishing its therapeutic potential. Pharmacological modulation of APOE via glucocorticoids, cytokine antagonists, or PPARγ agonists represents a novel strategy for early intervention in disc degeneration.